Study of dry ice formation during blowdown of COâ-CHâ from cryogenic distillation column - Shafiq, U. (Elsevier Ltd, 2020)
Cryogenic distillation columns are generally subjected to high-pressure loadings during the natural gas purification process. The high-pressure conditions inside the column cause safety risk e.g. rupture. When an emergency arises, blowdown is a typical way of minimizing the failure hazard. However, blowdown at the cryogenic conditions involves dry ice formation due to the rapid decrease in temperature driven by the Joule-Thomson effect. The dry ice formation intensifies the failure hazard due to the orifice blockage. Therefore, optimization of blowdown parameters is necessary to avoid the dry ice formation. So far, very limited studies are available in the literature for the blowdown of COâ-CHâ mixture, especially at the cryogenic conditions. In this study, a computational investigation followed by the experimental validation is accomplished to analyze the dry ice formation during blowdown of COâ-CHâ binary mixture from the cryogenic distillation column. The composition of mixture, orifice size, and initial conditions inside vessel have a high impact on blowdown path. A 3.00 mm orifice is the most suitable size for the blowdown at cryogenic conditions as it doesn't promote solidification and discharges the inventory quickly. Based on the experimental observation, an empirical correlation is also developed to instantly find out the optimum blowdown parameters. Â© 2020 Elsevier Ltd